The Thiadiazole Ring (THD) Is a Building Block for Potential Inhibitors of the SARS-CoV-2 Main Protease (Mpro): Theoretical Look into the Structure, Reactivity, and Binding Profile of Three 1,3,4-THD Derivatives toward Mpro - Dileep Chikkur Shanthakumar; Lohith Tumakuru Nagarajappa; Bienfait Kabuyaya Isamura; Mofeli Benedict Leoma; Kabelo Phuti Mokgopa; Sridhar Mandayam Anandalwar; Sahana Doreswamy; Srikantamurthy Ningaiah (Engineering Proceedings)
Thiadiazole (THD) derivatives are famous for their exceptional chemical properties and versatile biological activities. In this work, we report computational investigations of the structure, reactivity, and binding affinity of three 1,3,4-THD derivatives (THDs) toward the SARS-CoV-2 main protease (Mpro). Hirshfeld surface (HS) analyses are carried out in conjunction with topological calculations in the context of the quantum theory of atoms in molecules (QTAIM) and reduced density gradient (RDG) to unravel the nature and magnitude of noncovalent interactions that contribute to maintaining these THDs. The three approaches consistently indicate that the titled THDs are mainly stabilized by weak intramolecular H…H, C-H…π, C-H…N, and N-H..H interactions in their monomeric forms, while their dimers also exhibit intermolecular π…π stacking and T-shaped contacts. In addition, Hirshfeld atomic charges, frontier molecular orbitals (FMOs), Fukui functions, and molecular electrostatic potential (MEP) reveal that the pyrrolic H atom (ring F) and the imidazole N atom (ring E) are the preferred binding sites for nucleophilic and electrophilic attacks, respectively. Finally, docking and molecular dynamics simulations demonstrate the remarkable binding profile of THDs toward the Mpro, which can be related to potential inhibitory activity.